Prenatal and Postnatal Therapies for Down's Syndrome and Associated Developmental Anomalies and Degenerative Deficits: A Systematic Review of Guidelines and Trials - Hasina, Zinnat; Wang, Chi Chiu (Frontiers in Medicine, 2022)
Down’s syndrome (DS) is the most common genetic disorder at birth. Multiple developmental abnormalities before birth and early onset of degenerative deficits after birth are features of DS. Early treatment for the manifestations associated with DS in either prenatal or postnatal period may improve clinical outcomes. However, information available from professional bodies and to communities is very limited. We carried out a systematic review and attempted meta-analysis of clinical trials for developmental abnormalities and degenerative deficits in DS. Only 15 randomized controlled trials (RCTs) in 995 (24 days to 65 years old) individuals with DS showed some improvement in cognitive disorders, development and growth, and musculoskeletal problem. However, each trial used different parameters and methods to measure various outcomes. RCTs of prenatal interventions in fetus with DS are lacking. The efficacy and safety of specific interventions in DS are still largely unknown. Proper counselling of the potential treatment for pregnant mothers who wish to continue their pregnancy carrying fetus with DS, and to health care professionals who take care of them are not adequate nowadays.